ANALISIS PENGELOLAAN PELABUHAN PERIKANAN UNTIA SECARA TERPADU BERBASIS ECOFISHINGPORT - Hermin Lutfiah Mita Pratiwi; Danial Danial; Rustam Rustam (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2024)
The purpose of this study was to determine the management value of the Untia Fishing Port Area based on eco-fishingport parameters and to determine the status of the Untia Fishing Port Area management assessment. This study was conducted at the Untia Fishing Port from May to June 2023. The method in this study was carried out by going directly to the field and conducting interviews and questionnaire assistance with 25 respondents who were samples. The selection of respondents was carried out using the purposive sampling method, namely the selection of respondents deliberately through several considerations. The respondents selected were respondents who were directly involved or who were considered to have the ability and understand the problems related to the Untia Fishing Port and were able to answer the problem formulation of this study. Sampling using purposive sampling, namely sampling whose members were selected deliberately based on the knowledge and beliefs of the researcher. And analyzed with Likert Scale Analysis. Results of the study show that the assessment of eco-fishingport parameters for each aspect at the Untia Fishing Port produces an index value for the Physical Environment Aspect of 0.75, Socio-Economic Aspect of 0.15, Fishery Commodity Aspect of 0.51 and Supervision Aspect of 0.19, so the total index value of each parameter is 1.60 which is in the moderate category or requires improvement in all performance and aspects of port environmental control towards the criteria of an environmentally friendly port (eco-fishingport).